2020
DOI: 10.5664/jcsm.8128
|View full text |Cite
|
Sign up to set email alerts
|

Older adult US Medicare beneficiaries with untreated obstructive sleep apnea are heavier users of health care than matched control patients

Abstract: Study Objectives: To examine the effect of untreated obstructive sleep apnea (OSA) on health care utilization (HCU) and costs among a nationally representative sample of Medicare beneficiaries. Methods: Our data source was a random 5% sample of Medicare administrative claims data for years 2006-2013. OSA was operationalized as (1) receipt of one or more International Classification of Disease, Version 9, Clinical Modification diagnostic codes for OSA in combination with (2) initiation of OSA treatment with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Given this presumed high prevalence of undiagnosed and therefore untreated sleep disorders, there are potentially very significant societal implications in terms of reduced performance/productivity in school and the workplace 12 . Furthermore, the sleep disorders that are correlated with long‐term health consequences have been shown to significantly increase the burden on the healthcare system 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Given this presumed high prevalence of undiagnosed and therefore untreated sleep disorders, there are potentially very significant societal implications in terms of reduced performance/productivity in school and the workplace 12 . Furthermore, the sleep disorders that are correlated with long‐term health consequences have been shown to significantly increase the burden on the healthcare system 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…If adding those with low-grade sleep apnea, the prevalence figures are 59.4% and 33.2% respectively [3]. However, therapy for mild sleep apnea is only necessary in the case of cardiovascular risk or associated daytime sleepiness [4]. Due to limited diagnostic capacities, a high number of unrecognized cases have to be assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Wickwire and colleagues, using administrative data have shown the economic impact of obstructive sleep apnea (OSA) in older people. 1 Prior research has shown OSA confers an increased risk for cardiovascular and metabolic disease, [2][3][4][5] stroke, 6 psychiatric conditions 7 and death. 8 A growing literature has also documented greater economic burden for individuals with untreated OSA compared with matched controls without OSA.…”
mentioning
confidence: 99%
“…17 To build upon prior investigations that have found OSA to be associated with substantial economic burden, Wickwire et al has presented a rigorous analysis of the impact of untreated OSA on HCU among older adults in this issue of the Journal of Clinical Sleep Medicine. 1 Using data from a random sample of Medicare administrative claims for years 2006-2013, the authors demonstrated that untreated OSA in older adults was associated with increased HCU and higher costs across all points of service. 1 This study is notable for several reasons.…”
mentioning
confidence: 99%
See 1 more Smart Citation